1997
DOI: 10.1016/s0009-9236(97)90029-1
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of valsartan in patients with liver disease

Abstract: These data are consistent with the pharmacokinetics of valsartan in that biliary excretion is the main route of elimination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 9 publications
2
65
0
Order By: Relevance
“…14,15 In patients with mild to moderate hepatic disease, a two-fold increase in AUC is observed and the t . is prolonged, 14,15,156 but, no dosage adjustment is needed in such patients. 14,15 No pharmacokinetic data are available in patients with severe hepatic diseases.…”
Section: S79mentioning
confidence: 99%
“…14,15 In patients with mild to moderate hepatic disease, a two-fold increase in AUC is observed and the t . is prolonged, 14,15,156 but, no dosage adjustment is needed in such patients. 14,15 No pharmacokinetic data are available in patients with severe hepatic diseases.…”
Section: S79mentioning
confidence: 99%
“…It has been reported that lisinopril and quinapril hydrochloride are primarily eliminated in urine and that valsartan is not eliminated in urine (9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that lisinopril has a poor ability to bind to plasma protein and that quinapril hydrochloride and valsartan have a good ability to bind to plasma protein (9)(10)(11) and it has been shown that the halflife of lisinopril is longer than that of quinapril hydrochloride (9,10). We accordingly thought that lisinopril had a greater potential to induce adverse effects, such as angioedema, than did quinapril hydrochloride in the present case with severe renal impairment, because increased bradykinin levels appear to be one of the mechanisms underlying the development of ACE-I-associated angioedema.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic clearance is the primary route of elimination of valsartan (*83% of the dose) [37,99] and contributes to the clearance of sacubitril (37-48% of the dose; primarily as sacubitrilat). Compared with healthy subjects, in patients with mild and moderate hepatic impairment, AUCs increased by 1.5-and 3.4-fold for sacubitril, by 1.5-and 1.9-fold for sacubitrilat, and by 1.2-and 2.1-fold for valsartan, respectively [45].…”
Section: Patients With Hepatic Impairmentmentioning
confidence: 99%